Conservation of DNA sequences for plasmid-mediated citrate utilization within the enterobacteria. - Hirato, T (1986)
Southern blot DNA-DNA hybridization experiments with a cloned Cit+ DNA fragment as a probe showed that the plasmid-mediated Cit+ determinants from four Cit plasmids (R726, pOH3001, pOH3035, and pOH30221) were all homologous. Sequences homologous to the plasmid-borne Cit+ gene were also found in total bacterial DNA isolated from Salmonella paratyphi B, Salmonella enteritidis, Salmonella typhimurium LT-2, Citrobacter freundii, ATCC 8090, Citrobacter amalonaticus ATCC 25405, Klebsiella pneumoniae I and IID 977, and Enterobacter aerogenes ATCC 13048. The DNA digest from C. amalonaticus ATCC 25405 contained a 1.4-kilobase BamHI-HincII DNA fragment that was strongly homologous with and identical in size to the plasmid Cit+ probe.